Pengembangan Pantai Tanah Lot Sebagai Daya Tarik Wisata Berkelanjutan Di Desa Beraban Kecamatan Kediri Kabupaten Tabanan Bali - Samudra, I Wayan Teja; Kartimin , I Wayan; Putri, Ida Ayu Karina (Universitas Triatma Mulya, 2023)
In the current era of globalization, the development of world tourism can be made a top priority in supporting the development of a region. Tourism development is essentially to develop and utilize tourist attractions in the form of natural wealth, diversity of flora and fauna, cultural arts, historical heritage, ancient objects and cultural pluralism. It can be in the form of natural beauty, historic sites, ordinances of social life and religious ceremonies. The research entitled Development of Tanah Lot Beach as a Sustainable Tourist Attraction in Beraban Village, Kediri District, Tabanan Regency, Bali aims to determine the potential and development of Tanah Lot Beach. This research uses a qualitative descriptive approach with SWOT analysis. Data were collected by observation techniques, interviews and documentation studies. The informants interviewed included the village head and village officials, businessmen, community leaders, tourists and the people of Beraban Village. The conclusions from the results of this study are (a) Tanah Lot Beach, has beautiful, cool and pristine natural potential which provides comfort for visitors to tourism objects besides customs and culture, (b) strategies offered for use in the development of Tanah Lot Beach is the direction of environmentally friendly development by maintaining cleanliness and reducing plastic waste.